Synthesis, biophysical analysis and biological evaluation of tricyclic pyrones and pyridinones as anti-alzheimer agents - Rana, Sandeep (Kansas State University, 2009)
The objectives of this research project were to (i) synthesize different bicyclic and tricyclic pyrone and pyridinone compounds; (ii) study the mechanism of action of these compounds in solution as anti-Aβ (amyloid β) agents using different biophysical techniques; and (iii) study the biological activity of pyrone compounds for the counteraction of Aβ toxicity using MC65 cells, a human neuroblastoma cell line and 5X- familial Alzheimer’s disease (5X FAD, a transgenic mice with five different mutations) mice. A series of tricyclic pyrone and pyridinone compounds were investigated. The tricyclic pyrones and pyridinones were synthesized utilizing a condensation reaction between cyclohexenecarboxaldehye (25) and 4-hydroxy-6-methyl-2-pyone (24) or 4-hydroxy-6-methyl-2-pyridinone (51), respectively. A tricylic pyrone molecule CP2 (2, code name) was synthesized and has an adenine base unit attached to the pyrone core. For structure activity relationship (SAR) studies, the adenine group of CP2 was replaced with other DNA base units (thymine, cytosine and guanine) and various heterocyclic moieties. Since nitrogen containing compounds often exhibit increased bioactivity and brain-penetrating abilities, oxygen atom (O5’) was displaced with a nitrogen atom in the middle ring of the tricyclic pyrone. A condensation reaction of pyrone 51 and 25 was carried out to give the linear pyranoquinoline (52) and the L-shaped pyranoisoquinoline (53). The neurotoxicity of amyloid-β protein (Aβ) is widely regarded as one of the fundamental causes of neurodegeneration in Alzheimer’s disease (AD). Recent studies suggest that soluble Aβ oligomers rather then protofibrils and fibrils may be the primary toxic species. Different biophysical techniques including atomic force microscopy (AFM), circular dichroism (CD), surface plasmon resonance (SPR) spectroscopy, and protein quantification assays were used to study the mechanism of aggregation of Alzheimer Aβ peptide in solution. In search of potentially bioactive compounds for AD therapies, MC65 cell line was used as a screening model. Different tricyclic pyrone and pyridinone compounds protect MC65 cells from death. We studied the efficacy of CP2 in vivo by treatment of 5X FAD mice, a robust Aβ42-producing animal model of AD, with a 2-week course of CP2, which resulted in 40% and 50% decreases in non-fibrillar and fibrillar Aβ species respectively.
Keywords: Anti-Alzheimer agents; Tricyclic pyrone; Tricyclic pyridinone; Atomic force microscopy; MC65 cells; In vivo studies; Chemistry, Biochemistry (0487); Chemistry, Organic (0490); Chemistry, Pharmaceutical (0491)